1998
DOI: 10.1016/s0741-5214(98)70139-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tumor necrosis factor binding protein and interleukin-1 receptor antagonist on the development of abdominal aortic aneurysms in a rat model

Abstract: TNF-BP, but not IL-1RA, may inhibit the development of AAAs in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 10 publications
2
39
1
Order By: Relevance
“…Since this model exhibits several similarities with hu- man abdominal aortic aneurysms [5], various laboratories have used it to investigate the pathogenesis and prevention of aneurysm growth. Unfortunately, the mortality rate in this model has not been mentioned in previous reports [1][2][3][4][5][6][7][8][9][10][11]. Although 2 h of elastase infusion time and a 1-cm segment of aorta have been used in all studies since Anidjar et al first described this model in 1990 [1], we noted a high mortality rate in the experimental animals.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Since this model exhibits several similarities with hu- man abdominal aortic aneurysms [5], various laboratories have used it to investigate the pathogenesis and prevention of aneurysm growth. Unfortunately, the mortality rate in this model has not been mentioned in previous reports [1][2][3][4][5][6][7][8][9][10][11]. Although 2 h of elastase infusion time and a 1-cm segment of aorta have been used in all studies since Anidjar et al first described this model in 1990 [1], we noted a high mortality rate in the experimental animals.…”
Section: Discussionmentioning
confidence: 65%
“…The elastase-induced rat aneurysm model is one of a few established in vivo aneurysm models and is used in many laboratories [1][2][3][4][5][6][7][8][9][10][11]. Commonly the rats are given drugs containing anti-inflammatory agents before or after elastase infusion to investigate the pathogenesis and prevention of aneurysm formation.…”
Section: Introductionmentioning
confidence: 99%
“…Since this experimental model exhibits several similarities to human abdominal aortic aneurysms, 14 a variety of laboratories have used it to investigate the pathogenesis and prevention of aneurysm growth. 10,12,13,[15][16][17][18][19][21][22][23][24] In this study, we used a modification of the model that we recently described. 25 An inflammatory response is a critical step in this model.…”
Section: Discussionmentioning
confidence: 99%
“…8 An elastase-induced rat aneurysm model is commonly used to investigate the pathogenesis and prevention of abdominal aortic aneurysms. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] In this model, inflammatory cell infiltration of the aortic wall occurs in temporal relation to an increase in the aortic diameter. 9,11,13,14 Inflammatory cell infiltration is considered to be a critical step in the development of aortic aneurysms in these rats.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the critical role of inflammatory cytokines in the pathogenesis of AAA through animal models. For example, it was demonstrated thataneurysm formation was attenuated in an elastase-induced rat AAA model by blocking the action of tumor necrosis factor-α (TNF-α) [13]. Furthermore, inflammatory cells such as monocytes have an important role in AAA pathogenesis through the secretion and activation of MMPs [14].…”
Section: Introductionmentioning
confidence: 99%